A scoping study of cultural interventions to treat addictions in Indigenous populations: methods, strategies and insights from a Two-Eyed Seeing approach - Rowan, Margo; Poole, Nancy; Shea, Beverley; Mykota, David; Farag, Marwa; Hopkins, Carol; Hall, Laura; Mushquash, Christopher; Fornssler, Barbara; Dell, Colleen A (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background This paper describes the methods, strategies and insights gained from a scoping study using a “Two-Eyed Seeing” approach. An evolving technique, Two-Eyed Seeing respects and integrates the strengths of Indigenous knowledge and Western sciences, often “weaving back and forth” between the two worldviews. The scoping study was used to inform a tool for measuring the impact of culturally based addictions treatment services on wellness in Indigenous populations. It formed part of a three-year study, Honouring Our Strengths: Indigenous Culture as Intervention in Addictions Treatment. The scoping study identified and mapped literature on cultural interventions in addictions treatment, and described the nature, extent and gaps in literature. Methods Using a Two-Eyed Seeing approach, we adapted, applied and enhanced a common framework of scoping studies. In the end stage of the scoping review process, an Ad Hoc Review Group, led by our project Elder, reviewed and interpreted Indigenous and Western understandings within the mapped information. Elements of the scoping study were joined with results from community focus groups with staff at treatment centres. Results Two-Eyed Seeing contributed differently at each stage of the scoping study. In early stages, it clarified team expertise and potential contributions. At the mid-point, it influenced our shift from a systematic to a scoping review. Near the end, it incorporated Western and Indigenous knowledge to interpret and synthesize evidence from multiple sources. Conclusions This paper adds to the collective work on augmenting the methodology of scoping studies. Despite the challenges of a Two-Eyed Seeing approach, it enables researchers using scoping studies to develop knowledge that is better able to translate into meaningful findings for Indigenous communities.